Long Non-Coding RNA (lncRNA) and MicroRNA ( miRNA) in Cancer Management - Sofia Mubarika Haryana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
AbstractThe discovery of microRNA, a small non coding RNA, has shed light to the dark matters (98%) of the genome. This finding resulted in a Nobel Prize awarded to Fire and Mello in 2006. miRNA a small non coding RNA which played a very important role in regulating protein expression through 3”UTR or other binding places to mRNA target. miRNA have been considered as negative regulators of protein coding gene expression that may impact in cell differentiation, proliferation, survival and all fundamental cellular processes, also implicated in carcinogenesis. miRNA can be grouped into tumor suppressor miRNA (miRSuppressor) and oncogenic miRNA (OncomiR). miRSuppressor regulates protein expression through targeting oncogenic mRNA, meanwhile OncomiR target mRNA Tumor Suppressor. Evidence indicates that deregulation in genetic and epigenetic may cause overexpression of oncomiR and loss of expression of Tumor Suppressor miR. In addition to that, in recent years, evidences showed that cell-to-cell communication conducted via exosome, which is released from every cell in physiological and pathological conditions andconsidered as fingerprints of cell and its status. This is a paramount biomarker discovery in cancer. In subsequent years, a lot of research further performed for the development of new cancer therapy. Our team GenomiR present our preliminary data on several miRNA in cancers aimed to develop minimal invasive biomarkers in cancer. Recently, the long non coding (lnc) RNA, another class of non-coding RNA have also attracted interest from many scientists in the world. lncRNA have emerged as an essential regulator in almost all aspect of biology included carcinogenesis. lncRNA considered as emerging key player in non-coding world.nCRNA (miRNA and lncRNA) in the context of cancer management will be discussed in this presentation